Pengaruh Motivasi, Pengetahuan Dan Persepsi Terhadap Minat Berkarir Mahasiswa Di Perbankan Syariah - Alfina Ramayanti; Novi Khoiriawati (Jurnal Ilmiah Ekonomi Islam, 2023)
This study aims to examine the influence of motivation, knowledge and perception variables on students' career interests in Islamic banking. The sample of this research is Sayyid Ali Rahmatullah Tulungagung State Islamic University students majoring in Islamic Banking class of 2019 with a total of 122 students. The sampling technique in this study used a simple random sampling technique. Data analysis technique using multiple linear regression analysis. The results of this study indicate that (1) the variable of motivation influences the interest in a career in Islamic banking, (2) the variable of knowledge influences the interest in a career in Islamic banking, (3) the variable of perception influences the interest in a career in Islamic banking, and (4) the variable motivation , knowledge, and perceptions influence student career interest in Islamic banking. The existence of this research is expected to be a reference and scientific knowledge regarding Islamic banking and economics, as well as a material consideration for students in making choices for future work, due to limited human resources who are competent in the field of Islamic economics, especially Islamic banking.